A close look on the effect of polyethylene glycol on the levansucrase thermostability: a case study of Brenneria sp. levansucrase. (8th August 2019) - Xu, Wei; Zhang, Wenli; Guang, Cuie; Zhang, Tao; Mu, Wanmeng
Abstract: BACKGROUND: To increase the low residual activity of levansucrase during long‐time processing, an enhancement of its weak thermostability is needed. Here, the effect of metal ions and polyethylene glycol (PEG) on the thermostability of levansucrase from Brenneria sp. EniD312 were studied and evaluated. The residual activity was determined and the protein structure was evaluated by circular dichroism spectrum, fluorescence intensity (FI), and surface hydrophobicity ( S 0 ). RESULTS: As a result of incubation with 10% ( w / v ) PEG 4000, the enzyme activity was increased by 1.24‐fold. After incubation with 5% PEG 4000 for 6 h, the residual activity at 35 and 45 °C was decreased to 55% and 60% of the initial activity, with an increase of 1.2‐ and 3.3‐fold than the wild‐type enzyme. Furthermore, the random coil content of enzyme was decreased from 53% of the wild‐type enzyme to 33.9% of the PEG pre‐incubated enzyme. Additionally, the FI was maximally increased and the S 0 was decreased from 117 to 69. CONCLUSION: All of these results suggested that after incubation with PEG 4000, the secondary and tertiary structure of wild‐type enzyme could be greatly maintained and then its thermostability could be increased. This study was the first report on the enhancement of levansucrase thermostability by PEG incubation and might be a good guideline to other researches on levansucrase. © 2019 Society of Chemical Industry